2013
DOI: 10.1271/bbb.120923
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Induces Vascular Endothelial Growth Factor Expression in the Rat Placentain Vivoandin Vitro

Abstract: We investigated the role of nitric oxide (NO) in vascular endothelial growth factor (VEGF) expression in the rat placenta. A nitric oxide synthase (NOS) inhibitor, N(G)-nitro-L-arginine-methyl ester (L-NAME), was constantly infused into pregnant rats 6-24 h before sacrifice on gestational day (GD) 15.5. NO production declined to about 15% of the control level as monitored by NO trapping and electron paramagnetic resonance spectroscopy. VEGF mRNA expression was temporally decreased by L-NAME, but recovered to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…50,51 Butylscopolamine administration averted the late phase of colitis; that is, the DAI remained low and colonic mucosa ulceration was not observed, whereas the leakage of RITC-gelatin from vessels and arrest of cell proliferation in the crypt were still observed. The downregulation of iNOS by butylscopolamine might reduce VEGF-A expression, as reported by Abe et al 52 The inhibitory effect of butylscopolamine on DSS-colitis might be exerted partly by the downregulation of VEGF-A. These results suggest that neuronal iNOS participated in exacerbating inflammation and that butylscopolamine administration did not prevent the early phase of the DSS-induced colitis such as microangiopathy and hypoxia condition of tissues, but did inhibit the exacerbation of inflammation and vascular hyperpermeability by reducing neuronal excitation.…”
Section: Discussionsupporting
confidence: 60%
“…50,51 Butylscopolamine administration averted the late phase of colitis; that is, the DAI remained low and colonic mucosa ulceration was not observed, whereas the leakage of RITC-gelatin from vessels and arrest of cell proliferation in the crypt were still observed. The downregulation of iNOS by butylscopolamine might reduce VEGF-A expression, as reported by Abe et al 52 The inhibitory effect of butylscopolamine on DSS-colitis might be exerted partly by the downregulation of VEGF-A. These results suggest that neuronal iNOS participated in exacerbating inflammation and that butylscopolamine administration did not prevent the early phase of the DSS-induced colitis such as microangiopathy and hypoxia condition of tissues, but did inhibit the exacerbation of inflammation and vascular hyperpermeability by reducing neuronal excitation.…”
Section: Discussionsupporting
confidence: 60%
“…We showed that EC-specific VEGF levels decrease in the absence of iNOS expression or activity and increase in the presence of an NO donor, and that this occurs in direct correlation with metastatic success [11]. iNOS-dependent VEGF production has also been reported elsewhere [64, 69, 70]. …”
Section: Introductionmentioning
confidence: 69%
“…VEGF is an important growth factor for angiogenesis during lung development. It was reported that NO induces VEGF synthesis (37), and VEGF induces EPCs mobilization and migration and incorporation into damaged vessels (20). We Figure 6.…”
Section: Lung Enos and Vegf Were Increased When Combining Epcs Transpmentioning
confidence: 87%